Feasibility of USG ‐Guided Objective Initial Assessment of Pupillary Size and Pupillary Reflexes Versus Clinical Examination in Patients With Altered Mental Status: A Cross‐Sectional Study - Modi, Priyanka; Bhoi, Sanjeev; Aggarwal, Praveen; Nayer, Jamshed; Sinha, Tej Prakash; Ekka, Meera; Mishra, Prakash Ranjan; Kumar, Akshay; Pandey, Savan (Journal of ultrasound in medicine, 2024)
Pupillary assessment is an important part of the neurological assessment which provides vital information in critically ill patients. However, clinical pupillary assessment is subjective. The ultrasound-guided pupillary examination is objective. There are limited pieces of literature regarding its use in assessing patients with altered mental status. So, we studied the extent of agreement of B-mode ultrasound with clinical examination for assessment of the pupillary size and reflex in patients with altered mental status. The primary objective was to determine the extent of agreement between clinical examination and ultrasound-based examination for assessing pupillary reflex and size in patients with altered mental status in two settings (trauma and non-trauma patients). Exactly 200 subjects (158 males, mean [range] age 43.56 [18-92 years]) with no history of partial globe rupture or dementia were included in this cross-sectional study from March 2019 to March 2020. B-mode ultrasound was performed with the subject's eyes closed using a 7-12 MHz linear probe and a standardized light stimulus. ICC score, paired t-test, kappa, Wilcoxon signed-rank test, and Bland-Altman plots were used for statistical analysis. The clinical-USG agreement for pupillary light reflex examination (Pupillary Diameter [PD] at rest, after direct light stimulation [D ] and consensual light stimulation [C ]) was excellent (ICC, 0.93-0.96). The Kappa coefficient (0.74 ± 0.07) showed an agreement of 87.36% between clinical and USG examination for pupillary reflex (reactive or non-reactive). USG-guided pupillary examination proves to be a better adjunct to neurological assessment in patients with altered mental status.